Genomic landscape of inverted urothelial papilloma and urothelial papilloma of the bladder. Issue 3 (22nd April 2019) - Isharwal, Sumit; Hu, Wenhuo; Sarungbam, Judy; Chen, Ying‐bei; Gopalan, Anuradha; Fine, Samson W; Tickoo, Satish K; Sirintrapun, Sahussapont J; Jadallah, Sana; Loo, Florence L; Pietzak, Eugene J; Cha, Eugene K; et al.
Abstract: Inverted urothelial papilloma (IUP) and urothelial papilloma (UP) are rare urothelial neoplasms that typically follow a benign clinical course. Oncogenic mutations in FGFR3, HRAS, and the TERT promoter have been reported in these entities but no comprehensive molecular analysis has been performed. We sought to characterize the genomic landscape of IUP and UP using whole‐exome and targeted next‐generation sequencing. In IUP, 10 of 11 tumors harbored oncogenic hotspot mutations in HRAS and the remaining tumor had an oncogenic KRAS mutation. None of the IUP tumors harbored TERT promoter or FGFR3 mutations. In UP, 8 of 11 tumors had oncogenic KRAS mutations and two had oncogenic HRAS mutations. One UP tumor had oncogenic mutations in FGFR3, PIK3CA, and the TERT promoter, and arose in a patient with recurrent non‐invasive papillary urothelial carcinomas. In contrast to urothelial carcinoma, the APOBEC mutational signature was not present in any IUP and UP tumors, and oncogenic alterations in chromatin remodeling genes were uncommon in both IUP and UP. The current study suggests that IUP and UP are driven primarily by RAS pathway activation and lack the more common genomic features of urothelial cancers. Copyright © 2019 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.